Understanding Cyclotron Motion: A Visual Approach to Electron Dynamics in Electric and Magnetic Fields - Candraditya, Rizky; Ningtyas, Cheryl Puspa; Aziz, Muhammad Rafi Athallah; Fadilah, Lailatu Syifa; Maharatri, Annisa Dian; Gibran, Azril Maulana (MJI Publisher by PT Mitra Jurnal Indonesia, 2024)
Physics material is often material that is difficult for students to understand because of its abstract concepts, one of which is in the material of electric and magnetic fields that discuss the motion of cyclotrons in connecting theoretical concepts and practical applications. Cyclotron motion is accelerated by an electric field that is influenced by the Lorentz force on the combination of electric and magnetic fields. This paper is made with the aim to analyze and visualize the electric field and magnetic field around the cyclotron motion particles using Python animation. In this study, a helix-shaped trajectory is used to represent the movement of electron particles. The animation developed depicts the electric and magnetic field vectors moving around the helix trajectory. In running the particle trajectory animation, numerical equations are involved. The involved numerical equations are second-order ordinary differential equations. This research not only provides theoretical insights into the electrostatic and magnetostatic properties of electron particles but also provides effective visualizations for further education and research. The resulting animation facilitates to enhance the understanding of the concept of how electric and magnetic fields interact and move in the context of electron particles moving in a helix trajectory, opening up opportunities for further exploration in the development of knowledge related to cyclotron motion that is often difficult to understand only through theoretical approaches.